Impaired bone remodeling in children with osteogenesis imperfecta treated and untreated with bisphosphonates: the role of DKK1, RANKL, and TNF-α. Issue 7 (July 2016) - Brunetti, G.; Papadia, F.; Tummolo, A.; Fischetto, R.; Nicastro, F.; Piacente, L.; Ventura, A.; Mori, G.; Oranger, A.; Gigante, I.; Colucci, S.; Ciccarelli, M.; et al.
Abstract Summary In this study, we investigated the bone cell activity in patients with osteogenesis imperfecta (OI) treated and untreated with neridronate. We demonstrated the key role of Dickkopf-1 (DKK1), receptor activator of nuclear factor-κB ligand (RANKL), and tumor necrosis factor alpha (TNF-α) in regulating bone cell of untreated and treated OI subjects. These cytokines could represent new pharmacological targets for OI. Introduction Bisphosphonates are widely used in the treatment of children with osteogenesis imperfecta (OI) with the objective of reducing the risk of fractures. Although bisphosphonates increase bone mineral density in OI subjects, the effects on fracture incidence are conflicting. The aim of this study was to investigate the mechanisms underlying bone cell activity in subjects with mild untreated forms of OI and in a group of subjects with severe OI treated with cycles of intravenous neridronate. Methods Sclerostin, DKK1, TNF-α, RANKL, osteoprotegerin (OPG), and bone turnover markers were quantified in serum of 18 OI patients (12 females, mean age 8.86 ± 3.90), 8 of which were receiving cyclic intravenous neridronate, and 21 sex- and age-matched controls. The effects on osteoblastogenesis and OPG expression of media conditioned by the serum of OI patients and anti-DKK1 neutralizing antibody were evaluated. Osteoclastogenesis was assessed in cultures from patients and controls. Results DKK1 and RANKL levels were significantly increased both in untreated and in treated OI subjects with respect to controls. The serum from patients with high DKK1 levels inhibited both osteoblast differentiation and OPG expression in vitro. High RANKL and low OPG messenger RNA (mRNA) levels were found in lymphomonocytes from patients. High amounts of TNF-α were expressed by monocytes, and an elevated percentage of circulating CD11b-CD51/CD61+ osteoclast precursors was observed in patients. Conclusions Our study demonstrated the key role of DKK1, RANKL, and TNF-α in regulating bone cell activity of subjects with OI untreated and treated with bisphosphonates. These cytokines could represent new pharmacological targets for OI patients.